2003
DOI: 10.1097/01.ju.0000095474.86981.00
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Prostatic Protrusion Predicts the Outcome of a Trial Without Catheter Following Acute Urine Retention

Abstract: IPP is a useful predictor for evaluating the success of a voiding trial following ARU. Patients with a grade 1 prostate may benefit from a trial without a catheter. However, patients with a grade 3 prostate are less likely to do so and would require a more definitive surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 6 publications
5
83
1
2
Order By: Relevance
“…These include the volume drained [4][5][6] , age [6] , PSA [5] , intravesical prostatic protrusion [7] , urodynamic studies [6,8] and prostate size [3] . In this series, we have successfully been able to demonstrate 3 predictive values that will help in the future management of AUR.…”
Section: Discussionmentioning
confidence: 99%
“…These include the volume drained [4][5][6] , age [6] , PSA [5] , intravesical prostatic protrusion [7] , urodynamic studies [6,8] and prostate size [3] . In this series, we have successfully been able to demonstrate 3 predictive values that will help in the future management of AUR.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age and urinary retention volume were shown to be associated with increased risk of failed TWOC outcome [10] , but were not important in this study. Our study showed that constipation and prostatic symptoms measured by IPSS score were significant fac- [13,14] , serum PSA [16] and IPP grading [17] or measurement [18] were shown in other studies to be important predictors of failed TWOC after AUR. In particular, patients with IPP grade 3 ( 1 10 mm) on transabdominal ultrasound and who were Alfuzosin naïve were shown to have almost 70% chance of failure of TWOC [17] .…”
Section: Discussionmentioning
confidence: 72%
“…Our study showed that constipation and prostatic symptoms measured by IPSS score were significant fac- [13,14] , serum PSA [16] and IPP grading [17] or measurement [18] were shown in other studies to be important predictors of failed TWOC after AUR. In particular, patients with IPP grade 3 ( 1 10 mm) on transabdominal ultrasound and who were Alfuzosin naïve were shown to have almost 70% chance of failure of TWOC [17] . More recently, transrectal ultrasound was used to measure IPP in white males receiving Alfuzosin before TWOC and it was reported that men with IPP 1 10 mm were 6 times less likely to have a successful TWOC than those with IPP !…”
Section: Discussionmentioning
confidence: 72%
“…Patients with Grade 3 IPP were less likely to void compared to those with Grade 1 IPP (67% vs. 36%). (13) Thirdly, IPP can predict the progression of BPH. Patients with Grade 3 IPP were more likely to have clinical deterioration compared to those with Grade 1 IPP (44% vs. 6%) at a mean follow-up period of 32 months.…”
Section: Pathophysiology Of Bphmentioning
confidence: 99%